What is the mechanism of the fiber effect on the rheological behavior of cement paste with polycarboxylate superplasticizer?. (26th April 2021) - Zhang, Kun; Pan, Lisha; Li, Jiacheng; Lin, Chang
Graphical abstract: Highlights: The addition of fiber can promote the adsorption of PCE. Increased fiber length, dosage, roughness and hydrophilicity led to worse fluidity of the cement paste. Plant fiber has a significant influence on the performance of cement paste. Abstract: Compared with most common construction materials, fiber reinforced cementitious materials are well known to exhibit better physical, working and mechanical properties. In this study, three fibers were selected: polypropylene fiber (PPF) and polyvinyl alcohol fiber (PVAF), which represented synthetic fibers, and sisal fiber (SF), which represented natural fibers. Effects of these fibers on the flowability, rheological properties, and adsorption behavior of the cement paste with polycarboxylate superplasticizer (PCE) were investigated. Furthermore, the above experimental results were verified by measuring the contact angle of the fiber with water and PCE solution and the apparent morphology of the fiber. Results revealed that the addition of fibers significantly reduces the fluidity of the cement paste, while the yield stress and plastic viscosity of the cement paste increase with the addition of fibers. From the contact angle and scanning electron microscope, the surface of SF was relatively rough, and the contact angle of SF with water or PCE solution was the smallest. It can be concluded that the plant fiber has a significant influence on the fluidity and rheology of cement paste.